Computerized Assessment of Pedophilic Sexual Interest Through Self-Report and Viewing Time: Reliability, Validity, and Classification Accuracy of the Affinity Program. (June 2013) - Mokros, Andreas; Gebhard, Michael; Heinz, Volker; Marschall, Roland W.; Nitschke, Joachim; Glasgow, David V.; Gress, Carmen L. Z.; Laws, D. Richard
Affinity is a computerized assessment tool that combines viewing time and self-report measures of sexual interest. The present study was designed to assess the diagnostic properties of Affinity with respect to sexual interest in prepubescent children. Reliability of both self-report and viewing time components was estimated to be high. The group profile of a sample of pedophilic adult male child molesters ( n = 42, all of whom admitted their offenses) differed from the group profiles of male community controls ( n = 95) and male nonsexual offenders ( n = 27), respectively. More specifically, both ratings and viewing times for images showing small children or prejuvenile children were significantly higher within the child molester sample than in either of the other two groups, attesting to the validity of the measures. Overall classification accuracy, however, was mediocre: A multivariate classification routine yielded 50% sensitivity for child molester status at the cost of 13% false positives. The implications for forensic use of Affinity are discussed.